PRACTICAL EXPERIMENTAL STUDY ON INCREASING THE EFFICIENCY OF DUST COLLECTING EQUIPMENT (Uzbekistan Open Conference, 2025)
Conclusions based on the analysis of the results of theoretical and applied research carried out to improve the retention and efficiency of dust when cleaning the dust-air flow coming out in the processing of cotton raw materials. Based on the analytical analyzes carried out at the cotton cleaning enterprise, the analysis of the dust-air flow cleaning technology as well as the process of processing their existing devices and information on the study of the characteristics of air-dust flow and dust particles for the cleaning of dust particles caused by technological processes at the cotton cleaning enterprise production.